Utilization of Catalyst Waste Molinex (CWM) in concrete - Muhammad Afiq Bin Mhd Khazar, Muhammad Afiq (Universiti Teknologi Petronas, 2008)
Catalyst is being used by various kinds of industries and most of it are in process plant as booster for reaction.. After some time, the catalyst can no longer be used and then reprocessed is needed to make it become useful. Results of the process, another undesired product or catalyst wastes are being produced. These wastes are normally dumps into landfill but the increasing quantities and occupy big areas and poses into danger of nature pollution. Concrete technology currently focuses on the cement replacement material (CRM) in order to find alternatives for cement usage. Pulverized fly ash (PFA) and silica fume are the most common cement replacement material which being utilized from waste material. The contribution in term of strength, durability and permeability are the ultimate goal of collaborating with CRM besides the economical point of view. The main objective of this project is to observe the possibility of recycling the catalyst waste which is called `molinex' into concrete and cement mortar. The research is based on the contribution of waste molinex in mortar in term of compressive strength.T he approach used is to determine the oxide content of molinex and cementitious material (silica oxide) are expected from molinex. Scanning electronic microscope is employed to examine this waste. Study on molinex as sand and cement replacement is also conducted. Effects of both replacements on compressive strength are carried out at 3,7,28 days. In conclusion, it has found that molinex do contribute to the strength development of mortar according to experimental casting of molinex as sand replacement and cement replacement.